The Application of PROMETHEE Method in Determining Scholarship Recipients at University - Prima, Wahyu; Putra, Firmansyah; Sapriadi, Sopi; Hayati, Rahmatul (Universitas Muhammadiyah Malang, 2024)
This study aims to use PROMETHEE method as a decision support system in determining the recipients of the Academic Achievement Improvement Scholarship at Universitas Dharmas Indonesia (UNDHARI). The methodological steps include problem identification, analysis, goal setting, and the application of PROMETHEE method. In this study, the criteria and alternatives have been identified to evaluate the scholarship recipients. The criteria weights are set, and the criteria preference types are determined. After obtaining the baseline data from the questionnaire assessments, pairwise preference values and multicriteria preference index values are calculated. Then, the rankings are compiled using Leaving Flow, Entering Flow, and Net Flow methods, resulting in the priority order of the scholarship recipients. The ranking results show that alternative 3 (IS) has the highest Net Flow value (0.30), while alternative 2 (AV) has the lowest Net Flow value (-0.35). Thus, the priority order from highest to lowest is IS, AV, RD, YM, and AV. In the context of Net Flow scores, these results indicate that alternative 3 (IS) has the greatest chance of receiving the academic achievement improvement scholarship. This study provides important insights for UNDHARI in the scholarship recipient determination process using the PROMETHEE method as a decision-making tool.